EVALUATION OF THE IRON AND FOLIC ACID SUPPLEMENTATION PROGRAM AMONG ADOLESCENT GIRLS IN KARAWANG REGENCY, 2025 - Sugiharti, Eti; Kusumastuti, Istiana (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2026)
Brief background: Anemia remains a major public health issue among adolescent girls in Indonesia, including in Karawang Regency. To address this, the government implemented the Iron Supplementation Program (Tablet Tambah Darah/IFA) in schools through cross-sector collaboration between the Health Office and the Education Office. However, the rate of IFA consumption and reduction in anemia cases remain suboptimal. Research objectives: This study aims to evaluate the implementation of the IFA program for adolescent girls in Karawang based on the components of input, process, and output using SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis. Methods used: This is a qualitative study with a descriptive evaluative approach. Informants consisted of representatives from the Health and Education Offices, health center heads, nutrition officers, school principals, and school health teachers (UKS). Data were collected through in-depth interviews, observation, and documentation, and analyzed thematically with SWOT analysis. Summary of results: The findings show that the strengths of the program include policy support, availability of nutrition officers, and integration into the school health program (UKS). Weaknesses include low adherence among students, limited UKS facilities, and inconsistent reporting. Opportunities include national policy support, potential for cross-sector collaboration, and technological advances. Conclusion: Threats include negative stigma toward IFA, dependency on health personnel, and lack of support from some school principals. In conclusion, the IFA program in Karawang is supported structurally, but still faces challenges in implementation and adolescent participation. Strengthening cross-sector coordination and behavior change communication strategies is needed to improve program effectiveness.